(untitled) (RUNA, archivo para las ciencias del hombre, 2013)
Evaluadores Extranjeros Alicia González de Castells - UFSC, Brasil Jorge Alfredo Hidalgo Lehuede - UChile, Chile Maria Dolores Marrodán - UCM, España Eloísa Martín - UFRJ, Brasil Elizabeth Pissolato - UFJF, Brasil Henry Tantaleán - UNMSM, Perú Márnio Teixeira-Pinto - UFSC, Brasil Izabela Tomaso - UFRJ, Brasil Evaluadores Nacionales Gabriela Caretta - UNSa Delia Lomaglio - UNCa Carlos Masotta - INAPL